Lithium Niobate on Insulator: An Emerging Platform for Integrated Quantum Photonics. Issue 22 (12th September 2021) - Saravi, Sina; Pertsch, Thomas; Setzpfandt, Frank
Abstract: Due to its properties, lithium niobate is one of the most suitable material platforms for the implementation of integrated optical quantum circuits. With the commercialization of lithium niobate on insulator (LNOI) substrates in the recent years, the lithium niobate nanostructuring technology has progressed immensely. Now nanostructured LNOI components can be fabricated with a quality on par with any other material platform, and could act as effective building blocks for integrated quantum circuits. The advanced nanostructuring technology combined with its favorable material properties make the LNOI platform a real contender for the realization of large‐scale optical quantum circuits. The aim of this perspective article is to examine the utility of the LNOI platform toward this goal. To do this, first the availability of the individual components that can act as the building blocks for such circuits is investigated. Afterward, a fully on‐chip implementation of a multiplexed source of single photons on the LNOI platform is envisioned, which is a highly challenging task in all material platforms. Based on the performance of the state‐of‐the‐art components on the LNOI platform, the performance of such a device is quantified and the areas in which more progress is needed are pointed out. Abstract : This perspective article examines and consequently promotes the utility of the lithium niobate on insulator (LNOI) platform for integrated quantum photonics, by investigating the availability of the individual building‐block components for such circuits, and then quantifying the performance of an envisioned on‐chip quantum device based on the state‐of‐the‐art nanostructured LNOI components. Furthermore, areas that need more progress are pointed out.